Unearthing Vulnerability and Resilience of Novice EFL Teachers in Shaping Their Professional Identity - Sandy, Yuli Ari (JALL (Journal of Applied Linguistics and Literacy), 2024)
This study explored the experiences of novice English as a Foreign Language (EFL) teachers in both formal education (FE) and non-formal education (NFE) settings, with a focus on professional identity development. It examined how these experiences contribute to the formation of their professional identity with the research question: What is the impact of vulnerability and resilience on the professional identity development of novice EFL teachers in both FE and NFE settings? This qualitative research adopted a descriptive narrative approach. Data collection was through interviews and literature review. The data collected was analysed through the use of coding and triangulation techniques. Four novice EFL teachers, two of the FE teachers and two of the NFE teachers were selected to participate in this research. The findings identified four impacts of vulnerability and resilience on professional identity development of novice EFL teachers; 1) self awareness, 2) adabtability to challenges, 3) institutional support, and 4) professional commitment.